Concert repertoire for brass sextet with ad lib, parts for brass choirs, brass classes, and brass sections full score - BACH-ABERT (Rubank Inc., 1957)
AllerseelennBalladenChanson tristenChoralenChristmas serenadenJubileenMarche vaillant